2013
DOI: 10.5028/jatm.v5i1.233
|View full text |Cite
|
Sign up to set email alerts
|

Maximization of Fundamental Frequency of Laminated Composite Cylindrical Shells by Ant Colony Algorithm

Abstract: The success in developing modern aerospace systems addresses competitive subjects as optimization, reduced costs, sustainability, environment, weight, and safety. There is an increased demand for lighter materials such as laminated composites. In order to match the demand of aeronautical companies, the shell structures are very important. The dynamic behavior of composite structures is also essential to improve the potential applications of these materials. The knowledge of the dynamic response of the cylindri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…The optimization procedure described above, with GA as a tool to solve the optimization problem and ANN as a tool that substitutes time-consuming FE calculations, was verified using an example described in [41]. All of the following assumptions (regarding the FE model, material parameters, lamination angles, and so on) are based on this article.…”
Section: Verification Examplementioning
confidence: 99%
See 1 more Smart Citation
“…The optimization procedure described above, with GA as a tool to solve the optimization problem and ANN as a tool that substitutes time-consuming FE calculations, was verified using an example described in [41]. All of the following assumptions (regarding the FE model, material parameters, lamination angles, and so on) are based on this article.…”
Section: Verification Examplementioning
confidence: 99%
“…In order to verify the compatibility of MODEL3 with the FE model used by Koide and Luersen in [41], the fundamental natural frequency was calculated for three different stacking sequences described in [41] and compared with the values in that paper. The results, shown in Table 1, prove that the proposed FE model and the FE model in [41] can be considered compatible. The optimization of the lamination angles in order to obtain the maximum value of the fundamental natural frequency f 1 was performed according to the scheme shown in Figure 2.…”
Section: Verification Examplementioning
confidence: 99%
“…The optimization of laminated composite cylindrical shell under different load and pressure has already been highly regarded in literature Haftka and Riche, 1993;Onoda, 1985;Abdi et al, 2012;Koide and Luersen, 2013;Almeida and Awrucha, 2007;Topal, 2011;Raju and Rao, 2015 . In these researches, mass and cost of shell, strength and stiffness, frequency and stability can be function for optimizing.…”
Section: Introductionmentioning
confidence: 99%
“…If this requirement is practically unattainable, then the fundamental frequency is required to lie between two excitation frequencies. Koide R & Luersen M [13] proposed the use of an ant colony algorithm to maximize the fundamental frequency of laminated composite cylindrical shells. It Sadr et al [14] presented a new method to optimize constant-stiffness composite plates for maximum fundamental frequency using a combination of Elitist Genetic algorithm and finite strip method.…”
Section: /4mentioning
confidence: 99%
“…This implies that there is an opportunity to optimize the orientation of the fibers to obtain composite structures that outperform unidirectional fiber lay-ups. Studies have shown that in-plane optimal fiber orientation can increase structural stiffness [5][6][7], failure loading [8][9][10] and buckling stress [11][12][13], and improve the fundamental frequency of the laminate [14][15][16][17] over the traditional quasi-isotropic fiber construction without increasing the weight.…”
Section: Introductionmentioning
confidence: 99%